2005
DOI: 10.1111/j.1365-2672.2005.02667.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quinolone treatment on selection and persistence of quinolone-resistant Escherichia coli in swine faecal flora

Abstract: Aims: To study the effect of oral administration of a quinolone on emergence of resistance in an indicator bacterial species from faecal flora. Methods and Results: Quinolone resistance was studied in Escherichia coli obtained from the faecal contents of pigs housed in nine commercial farrow-to-finish herds in France after administration of flumequine to sows. The percentage of quinolone-resistant E. coli increased in the faeces of sows after administration of flumequine (mean 21AE78% at day 7 vs 6AE42% before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
1
8
2
1
Order By: Relevance
“…Intensive use of quinolones in the treatment of infections in humans and animals has led to the spread of resistant bacteria [10,11]. The increasing prevalence of infections caused by antibiotic-resistant bacteria makes empirical treatment of these infections more difficult [12].…”
Section: Discussionmentioning
confidence: 99%
“…Intensive use of quinolones in the treatment of infections in humans and animals has led to the spread of resistant bacteria [10,11]. The increasing prevalence of infections caused by antibiotic-resistant bacteria makes empirical treatment of these infections more difficult [12].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated above, these fluctuations were correlated with counts of ampicillin-resistant Enterobacteriaceae. Similarly, Belloc et al (2) studied the effect of quinolone treatment on the selection and persistence of quinolone-resistant E. coli in swine fecal flora and observed great variability in both the percentages of resistant strains and the patterns of emergence of resistance. In the present study, despite the great variability and the small number of pigs per mode of treatment, at least two of the three modes of drug administration (i.e., the intramuscular route and the oral route in fed pigs) could be differentiated by quantifying the bla TEM genes excreted in feces, but not by phenotypic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…22,51 Experimentally, antimicrobial exposure increases the prevalence of resistant E. coli in healthy pigs. 7,16,30 On-farm studies have also shown antimicrobial use is associated with E. coli AMR. 2,19,21 Observational studies are ideal for investigating complex problems with many causes or hypotheses.…”
Section: Introductionmentioning
confidence: 96%